Comparative Study of Outcome of Early Versus Delayed Closure of Loop Ileostomy in Cases of Enteric Perforation - Javed, Muhammad Asad; Amjad, Maheer; Ashraf , Muhammad Waseem; Yar , Muhammad Mohsin; Salah-U-Din, Muhammad; Parveen , Aamira (Indus Journal of Bioscience Research, 2025)
Background: When patients arrive late in their illness, ileostomy is frequently performed to prevent primary closure in emergency surgical situations such as enteric or tubercular perforations. But there are several morbidities associated with ostomy, which lowers quality of life. Early ostomy closure can reduce related morbidity and let the patient to experience improved quality of life sooner. Objective: To compare the outcome of early versus delayed closure of loop ileostomy in cases of typhoid perforation. Material & Methods: The study was a randomized controlled trial conducted at Jinnah Hospital's General Surgery Department, Lahore, over six months. 190 patients were enrolled, with 95 in each group. Patients were divided into two groups using a lottery method: early closure (Group A) and delayed closure (Group B). Post-operatively, patients were maintained on antibiotics for 10 days. Data was collected using a pre-designed proforma, and outcomes were recorded according to the operational definition. Results: A study of 190 patients, with a mean age of 38.58±5.96 years, found that 44.7 % were male and 65.3% were female in the early closure group, and 55.3 % were male and 34.7% were female in the delayed closure group. Wound infection was 38.3% in the early closure group and 61.7% in the delayed closure group, with no mortality in the early closure group and four in the delayed closure group. Conclusion: If patients are carefully chosen, the current study shows the potential benefits of early closure of loop ileostomy and provides a workable substitute for a more traditional delayed method.